2016
DOI: 10.1007/s12105-016-0751-4
|View full text |Cite
|
Sign up to set email alerts
|

Anaplastic Transformation of Papillary Thyroid Carcinoma Only Seen in Pleural Metastasis: A Case Report with Review of the Literature

Abstract: Anaplastic transformation of papillary thyroid carcinoma (PTC) at distant metastatic sites is extremely rare, and there have been fewer than 20 reported cases in the literature. A 61-year-old woman presented with 1-week history of dyspnea. Her past medical history was remarkable because, 19 years ago, she underwent nearly total thyroidectomy and radical neck dissection due to PTC. Computed tomography of the chest revealed a 1.7 cm nodule in the lung and diffuse pleural thickening. Gun biopsy of the lung nodule… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
18
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(20 citation statements)
references
References 19 publications
1
18
0
Order By: Relevance
“…However, as this is a rare condition, standard therapy has not yet established. This case report documents our clinical experience, we present herein a patient with pleural fluid due to papillary thyroid cancer, and reviewed previously reported such cases (3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19).…”
Section: Introductionsupporting
confidence: 73%
See 2 more Smart Citations
“…However, as this is a rare condition, standard therapy has not yet established. This case report documents our clinical experience, we present herein a patient with pleural fluid due to papillary thyroid cancer, and reviewed previously reported such cases (3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19).…”
Section: Introductionsupporting
confidence: 73%
“…Lung metastases of thyroid cancer are those to the lung parenchyma, such metastases usually have multiple small nodules in both lungs (1,2). On the contrary, however, pleural fluid due to thyroid cancer is a rare etiology, to our knowledge, and only 51 cases have been reported (3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19). Pleural fluid due to thyroid cancer has been reported to be less than 1% in all the patients with malignant pleural fluids (4,11).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…2 Kim et al reviewed fewer than 20 reported cases of anaplastic transformation at different metastatic sites and found only one case of pleural thickening with pleural effusion in which diagnosis was made by pleural biopsies with immunohistochemical staining suggestive of both PTC and anaplastic components. 3 In our case, the clinical work-up was led by the diagnosis of a pleural exudate in an asbestos-exposed patient with a PET-CT evaluation mimicking a malignant pleural mesothelioma. It highlights the diagnostic difficulties in such situations of malignant pleural effusion in a patient with a previous history of PTC, in particular when a thoracoscopic assessment of the pleural cavity is not feasible.…”
Section: Discussionmentioning
confidence: 85%
“…Kim et al . reviewed fewer than 20 reported cases of anaplastic transformation at different metastatic sites and found only one case of pleural thickening with pleural effusion in which diagnosis was made by pleural biopsies with immunohistochemical staining suggestive of both PTC and anaplastic components …”
Section: Discussionmentioning
confidence: 99%